2003
DOI: 10.1016/s0042-6822(02)00088-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum immunoglobulin A (IgA)-mediated immunity in human immunodeficiency virus type 2 (HIV-2) infection

Abstract: In the present study, we sought to define the importance of serum IgA (sIgA)-mediated immunity in HIV-2 infection. Serum samples from a total of 29 HIV-2-infected patients from Guinea-Bissau (n = 20) and Portugal (n = 9) were studied. Samples from seronegative individuals were used as controls. Antibody reactivity to native and recombinant envelope glycoproteins as well as peptides representing various regions of the envelope glycoproteins was investigated. Furthermore, the capacity of purified IgA to neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…We have recently shown that HIV-2-specific serum IgA has the capacity to neutralize a well-documented HIV-2 strain, SBL6669. The serum IgA primarily bound a region within the HIV-2 transmembrane gp36 (amino acids 644 to 658) (35). Taken together, the results of HIV-1 and HIV-2 studies indicate that HIV-specific IgA immune responses directed against envelope proteins with neutralizing capability may be important in host-pathogen interactions.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…We have recently shown that HIV-2-specific serum IgA has the capacity to neutralize a well-documented HIV-2 strain, SBL6669. The serum IgA primarily bound a region within the HIV-2 transmembrane gp36 (amino acids 644 to 658) (35). Taken together, the results of HIV-1 and HIV-2 studies indicate that HIV-specific IgA immune responses directed against envelope proteins with neutralizing capability may be important in host-pathogen interactions.…”
mentioning
confidence: 81%
“…IgA was purified from serum on Artocarpus integrifolia agglutinin (Jacalin; Vector, Burlingame, Calif.), and IgG was purified on protein G-Sepharose (Pharmacia, Uppsala, Sweden) as previously described in detail (35). Briefly, a 200-l volume of Jacalin-agarose beads was added to 20 l of serum diluted 1:10 in dilution buffer (2% [vol/vol] Triton X-100, 150 mM NaCl, 600 mM KCl, 5 mM disodium EDTA, pH 7.8).…”
Section: Study Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, six immunogenic regions have been identified in the HIV-2 envelope glycoproteins. Three of them are in gp125 (amino acids 234 to 248 in C2, 296 to 337 in V3, and 472 to 507 in C5), and the others are in the ectodomain of gp36 (amino acids 573 to 595, 634 to 649, and 644 to 658) [42][43][44][45][46][47][48][49][50]. Recently, Barroso and his co-workers have shown that the HIV-2 C2 and C3 are well exposed in the envelope complex and are under strong diversifying selection [41].…”
Section: Introductionmentioning
confidence: 99%